POTENSI EKSTRAK ETANOL DAUN SAMBILOTO (Andrographis paniculata (Burm. f.) Nees) TERHADAP INDUKSI APOPTOSIS PADA SEL RAJI In vitro - Dewi Hestiara Safitri (FKG 16 UMY 065, 2016)
Cancer is one of the leading causes of death in the world. Raji cells is a cell which come from lymphocyte B cancer. Cancer therapies such as chemotherapy, surgery, radiotherapy, and combination therapy has many side effects. Herbal therapy for cancer has an advantages in an economical way and minimum side effect. Sambiloto leaves (Andrographis paniculata (Burm. f) Nees) is a herb with andrographolide substance as it’s anticanter. The purpose of this study is to test the potency of ethanolic extracts of sambiloto leaves on apoptosis induction of raji cells. The method of this study is an in vitro pure laboratory experiment. Raji cells were given with six concentrations of ethanolic extracts of sambiloto leaves (Andrographis paniculata (Burm. f) Nees) which were 0; 3,125; 6,25; 12,5; 25 and 50 μg/ml. Apoptosis testing using double staining method with ethidium bromide and acridine orange. Observed the cells in the fluorescence microscope. Cells counting using one way anova. The result of this study ethanolic extract of sambiloto leaves (Andrographis paniculata (Burm. f) Nees) had a potency on inducting apoptosis of raji cells in 12,5 μg/ml with the average of cell apoptosis is 32,60%. The conclusion is ethanolic extract of sambiloto leaves (Andrographis paniculata (Burm. f) Nees) were effective on inducting apoptosis on raji cells.